Evaluation of the Budget Allocation Policy on Improving the Quality of High School and Vocational High School Education in Kutai Kartanegara Regency - Heriman Heriman; Widyatmike Gede Mulawarman; Warman Warman (EduLine: Journal of Education and Learning Innovation, 2022)
This study aims to describe the implementation and evaluation of budget allocation policies for high school and vocational education in Kutai Kartanegara Regency and what obstacles are faced by the government in the education budget allocation policy. This study uses a qualitative approach with the policy evaluation method Context, Input, Process, Product (CIPP) model. Data collection in the study involved ten participants consisting of the Head of the Education and Culture Office of East Kalimantan, Member of Commission IV of the DPRD of East Kalimantan Province. Principal of SMAN 1 Tenggarong, Principal of SMAN 2 Tenggarong, Principal of SMAN 3 Kota Bangun, Principal of SMAN 2 Tenggarong Seberang, Principal of SMAN 1 Muara Badak, Principal of SMKN 3 Tenggarong, Principal of SMKN 1 Tenggarong Seberang, and Principal of SMKN 2 Sebulu. Data collection methods are observation, interviews, and documentation. The process of data analysis was carried out through the stages of reduction, presentation, and conclusion drawing as well as analysis of the evaluation of the CIPP model. The results of this study indicate that: (1) The implementation of the education budget allocation policy in Kutai Kartanegara Regency is carried out by the East Kalimantan Provincial Government through the Department of Education and Culture by allocating a budget for the education sector of Rp 2.1 trillion. The budget is used by the Department of Education and culture with 2 expenditure compositions, namely direct expenditure, and indirect expenditure; (2) Based on the evaluation, decisions can be formulated into 4, namely: decisions on planning, decisions on procedures, decisions on implementation and decisions on follow-up; (3) The obstacle faced is the limited number of activity items, especially the existence of policies that regulate budget proposals for schools which must be based on the number of students. This causes delays and delays in the construction and development of schools that have a shortage of students.